Morphological change of shed and the effect of VEGF on amniotic membrane scaffold - Md Hashim, SN; Yusof, MFH; Alshehadat, SA; Kannan, TP; Suzina, SAH; Mokhtar@Makhtar, Khairani Idah; Azlina, A (Universiti Putra Malaysia, 2015)
Angiogenicity is one of the essential components to enable tissue function. It is important to develop a construct that would help in catering oxygen and nutrient to the engineered tissue area. Thus, this study aims to investigate the attachment, spreading and growth of stem cells from human exfoliated deciduous teeth (SHED) on human AM (HAM) with or without vascular endothelial growth factor (VEGF) using scanning electron microscope (SEM), and indirectly see the potential of the HAM as a scaffold to promote angiogenic micro-environment. Since day 1, there were continuous changes of the cell morphology until day 28, SHED treated with VEGF seemed to change its shape from fibroblast-like into a round-shape cell, similar structure as an endothelial-like cell. The structures of filopodia-like were also observed on the treated SHED. SHED without VEGF treatment showed only normal morphological growth on HAM. VEGF is a protein produced to stimulate angiogenesis, and is believed to contribute to the morphological changes of SHED seeded on HAM. This indicates that HAM could be used as a scaffold to allow SHED differentiation into endothelial-like cells with the induction of VEGF.